Erythrodermic pityriasis rubra pilaris managed at home: intensive community care followed by ustekinumab. (20th May 2018) - Ismail, N.; Callander, J.; Williams, M.; Anstey, A. V.
Abstract : Clickhere for the corresponding questions to this CME article.